Successful rechallenge of cetuximab following severe infusion-related reactions: a case report - Chang, Pei-Hung; Huang, Jen-Seng (Chinese Journal of Cancer Research; Vol 26, No 1 (February 27, 2014): Chinese Journal of Cancer Research, 2014)
Cetuximab, an anti-epidermal growth factor receptor (EGFR) monoclonal antibody, is associated with a risk of infusion reactions, similar to other infusional agents. Although avoiding a rechallenge with cetuximab following a severe infusion reaction is preferable, this may not be an option if few other reasonable alternatives exist. We report herein a successful case of cetuximab rechallenge, carried out by extending infusion times and using saline dilution in a patient who had severe infusion reactions twice and who required continuation of treatment. Cetuximab reintroduction with saline dilution and a slower infusion rate in an intensive care setting allowed safe continuation of therapy.